ADULT PHYSICAL ACTIVITY, SEDENTARY BEHAVIOUR AND SLEEP QUALITY IN THE DIGITAL TRANSFORMATION ERA - Fernāte, Andra; Vazne, Žermēna; Zuša, Anna; Bula-Biteniece, Inta; Dravniece, Irena; Grants, Juris; Žīdens, Janis; Jakovļeva, Monta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The digital transformation era increases population health risks associated with lack of exercise, as well as emphasizes the role of an active lifestyle within sustainable socio-economic development. Digitalization is one of the main reasons for setting significant public health priorities: poor or insufficient sleep and physical inactivity. The aim of the research was to study the physical activity (PA), sedentary behaviour (SB) and sleep duration of the population measured by a tri-axial accelerometer. Methods: The study is based on the project “EUPASMOS”, where PA, SB, and sleep-time of the participants (n = 369) was measured 24/7 by a tri-axial accelerometer (UKK RM42, UKK Terveyspalvelut Oy, Tampere, Finland) for a week-long period. The participants mostly spent their waking hours in a sedentary state. The mean duration of sedentary behaviour was 7h 52min. The participants took an average of 9584 steps a day. They also engaged in light PA for 4h 15min, and moderate-to-vigorous PA for 1h 16min. The mean duration of sleep was 5h 46min. The results showed that the insufficient sleep and physical inactivity of the participants are serious health risks in the digital transformation era. Future research should focus on the effect that various components of physical activity (dose, mode, timing) have on sleep.